A systematic review of robotic surgery: From supervised paradigms to fully autonomous robotic approaches - Han,J; Davids,J; Ashrafian,H; Darzi,A; Elson,DS; Sodergren,M (International Journal of Medical Robotics and Computer Assisted Surgery, 2022)
BackgroundFrom traditional open surgery to laparoscopic surgery and robot-assisted surgery, advances in robotics, machine learning, and imaging are pushing the surgical approach to-wards better clinical outcomes. Pre-clinical and clinical evidence suggests that automation may standardise techniques, increase efficiency, and reduce clinical complications.MethodsA PRISMA-guided search was conducted across PubMed and OVID.ResultsOf the 89 screened articles, 51 met the inclusion criteria, with 10 included in the final review. Automatic data segmentation, trajectory planning, intra-operative registration, trajectory drilling, and soft tissue robotic surgery were discussed.ConclusionAlthough automated surgical systems remain conceptual, several research groups have developed supervised autonomous robotic surgical systems with increasing consideration for ethico-legal issues for automation. Automation paves the way for precision surgery and improved safety and opens new possibilities for deploying more robust artificial intelligence models, better imaging modalities and robotics to improve clinical outcomes.